2019
DOI: 10.1007/s00520-019-04844-8
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care preferences for people with advanced cancer and their families in intensive care units: a systematic review

Abstract: Background: Advanced cancer patients' end-of-life care preferences in oncology units, medical-surgical units, nursing homes and palliative care services have been established. However, less is known about end-of-life care preferences of patients with advanced cancer in intensive care units and their families. Aim: To explore end-of-life care preferences of patients with advanced cancer and their families in intensive care units and if these align with essential elements for end-of-life care. Design: Electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Up until now, EOL preferences among patients with cancer have been explored in some countries and regions. [15][16][17][18][19][20][21] These studies identified the preferences of patients with cancer for EOL treatment, communication, decision-making and place of care and death. Results showed that more patients with cancer preferred comfort care and maintaining their quality of life in EOL.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Up until now, EOL preferences among patients with cancer have been explored in some countries and regions. [15][16][17][18][19][20][21] These studies identified the preferences of patients with cancer for EOL treatment, communication, decision-making and place of care and death. Results showed that more patients with cancer preferred comfort care and maintaining their quality of life in EOL.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, multiple studies have noted that a majority of patients prefer to die outside of the hospital with minimal emergency department (ED) visits and hospitalizations at EOL. [5][6][7] Such high-intensity care may also complicate grief for family members, as avoidance of both ICU admission and in-hospital death is associated with higher quality EOL care assessments among surviving family members. 8 Previous studies on MCCs in patients with cancer have largely focused on the link between MCCs, subpar chemotherapy receipt, and increased chemotherapy toxicity.…”
mentioning
confidence: 99%
“…Twenty-seven reviews identified barriers and enablers to providing patient-centred end-of-life care. [41][42][43]58,[62][63][64]66,68,77,78,80,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] These barriers and enablers were divided into three categories: (1) system factors; (2) staff factors; and (3) patient factors.…”
Section: Klop Et Al 55mentioning
confidence: 99%
“…58,80,88,91,93,98 Greater continuity and coordination of care, as well as improved communication systems between healthcare professionals, offers the opportunity for care that is consistent with patient preferences. 58,88,93 Regular documentation of a patient's symptoms and preferences, initiated early, was vital to the management and coordination of appropriate care planning, 41 however inconsistent documentation procedures and requirements, as well as the absence of agreed upon data storage locations, was found to contribute to time consuming and burdensome processes for staff due to competing responsibilities, 91 resulting in fragmented healthcare systems where information about a patient's preferences is not easily accessible. 87 Physical care environment.…”
Section: System Factorsmentioning
confidence: 99%